Linguistic Misogyny as a Parodic Device: Valspeak Markers in Jimmy Fallon’s “Ew!” - Pierre Habasque (Anglophonia)
The aim of this paper is to explore how markers of an enregistered sociolect perceived as feminine may be recruited to portray stereotypical female teenage characters on television. The analysis focuses on ‘Valley Girl talk,’ also known as Valspeak, popularized in the 1980s in California by Frank Zappa’s eponymous hit song, which parodied the sociolect. The corpus is composed of a sketch entitled ‘Ew!’, featured in The Tonight Show Starring Jimmy Fallon, in which the host dresses up as a teenage girl, Sara, chatting with her friend Addison (John Cena). Two main points are made. First, it is suggested that Fallon uses Valspeak markers, as well as linguistic features which may be perceived as feminine, in order to portray ‘girl talk’ on screen. Such features include lexical items, higher fundamental frequency, a prosodic contour (High Rising Terminal), a voice quality (creaky voice), and a shift in vowel quality. Second, the main goal of the sketch is to make the audience laugh, and its parodic power partly relies on the fact that semantic bleaching is used to orchestrate a loss of meaning in the discourse of the two characters. It is suggested that this stereotypical depiction of female characters’ use of language may be a case of ‘linguistic misogyny,’ i.e. stigmatizing an individual’s linguistic practices because they are (possibly wrongly) perceived as feminine.